25 Years After the USSR: Prospects of the Comparative Studies of Capitalism - Zhikharevich, Dmitrii (Journal of Economic Sociology, 2018)
This paper is an extended review essay dedicated to the special issue of Comparative Sociology “25 Years After the USSR” (2017, vol. 16, issue 1). The issue consists of 6 original research papers that are of interest for scholars working in the field of economic sociology. The paper shows how the topic of post-Soviet transformations still remains relevant for economic sociologists, and highlights the advantages and the shortcomings of the articles presented in the issue of Comparative Sociology. The paper also demonstrates how the fall of the USSR and the disciplinary rearrangement of the social sciences, economic sociology in particular, are related to the dominance of sociology of market as a research program. In short, the historical victory of the market capitalism allowed market exchange to be treated as a paradigm of social action. The consequence of this has been twofold: on the one hand, economic sociology has increasingly concerned itself with the study of markets, however, with a particular focus on the social structures that allow, make possible, and enhance market exchanges. On the other hand, this focus on the “scaffolding” structures of the markets made economic sociology an addition, instead of a competitor, to the neoclassical economic theory. The paper briefly reviews the arguments that support such a conclusion. In the final section, the paper analyses the limits of the strategy of comparative analysis of capitalisms in different countries that is being pursued by the articles presented in the issue under review.